Budgetary Slack Will Not Let Organization Die: Explaining Motivational and Stewardship Aspects of Conditional Slack - Rohma, Frida Fanani; Chamalinda, Khy'sh Nusri Leapatra (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 18 No 1 (2023)DO - 10.24843/JIAB.2023.v18.i01.p02, 2023)
The study aims to explore the motivational and stewardship aspects of managing budgetary slack. The stream of research demonstrates that budgetary slack is one of the dysfunctional behaviours which may be detrimental to an organization. The research delivers empirical evidence that organizations in the Boston Quadrant Matrix “Dogs” position are inclined to deliberately carry out additional financial resource budgeting through budgetary slack mechanism through cost assumption. The research used a qualitative method using a study-case approach and interpretive paradigm. The research area was a business industry in the Boston Quadrant Matrix “Dogs” position. The results indicate budgetary slack’s motivational aspects prompting the management to more significantly orient instead of only achieving cost budgeting targets. Cost budget target fulfilment could have been more rational when confronting non-financial orientations, i.e., product quality and going concerned. It accorded with stewardship theory that budgetary slack facilitated the management facing other goals besides budget-related ones. This research expands on previous research by showing that budgetary slack allowed the management to balance goals when external conditions change. It was a deliberate product, even a base for a budgeting system through its underlying cost assumption. Keywords:  budgetary slack, quadrant boston matrix, budgeting, going concern, stewardship